Features of the use of the numeral five in Tuvan linguoculture (as contrasted to a number of Turkic and Mongolian languages) - Bredis, Mikhail A.; Novospasskaya, Natalia V. (The New Research of Tuva, 2023)
The article examines Tuvan phraseological units and folklore texts that comprise the number of five. These examples were selected by continuous sampling from dictionaries and collections of folklore works. Five as a component of the numerical code of Tuvan culture is analyzed and compared to this numeral in the Khakas, Altai, Mongolian, Kalmyk and Buryat languages. In this work, we used a set of linguoculturological, descriptive and analytical methods. It has been found out that the frequency of use of the component and numeral “five” and the strength of its symbolism in Tuvan phraseology and folklore are significantly inferior to those of the number of five in the Mongolian languages. The same applies to the number of five among the Turkic peoples living in the Sayano-Altai region (the Khakas and Altaians). In Tuvan phraseology, the number of besh, not being sacred and having no significant power of symbolism, still plays a certain role. It symbolizes a large number or long time periods. In addition, the numeral is associated with the oldest image of the five fingers, as evidenced by the common Turkic and Mongolian paroemias with this image. The authors note the influence of the Mongolian culture on the Tuvan one. This explains the similarity of the symbolism of the number of five, which can be proved by the kinship of the Turkic and Mongolian languages within the Altai macrofamily of languages, as well as the length of the common history and linguistic and cultural transfer.